Functional Olfactory Sensory Neurons Housed in Olfactory Sensilla on the Ovipositor of the Hawkmoth Manduca sexta - Klinner, Christian F.; König, Christopher; Missbach, Christine; Werckenthin, Achim; Daly, Kevin C.; Bisch-Knaden, Sonja; Stengl, Monika; Hansson, Bill S.; Große-Wilde, Ewald (Frontiers in Ecology and Evolution, 2016)
Olfactory systems evolved to detect and identify volatile chemical cues, in many cases across great distances. However, the precision of copulatory and oviposition behaviors suggest that they may be guided by olfactory cues detected by sensory systems located on or near the ovipositor. Here we present evidence of a small number of functional olfactory sensilla on the ovipositor of the hawkmoth Manduca sexta. Gene expression analysis of isolated ovipositor tissue indicated active transcription of gustatory and both classes of olfactory receptor genes. Expression of the olfactory co-receptor ORCo and the antennal ionotropic co-receptors IR8a and IR25a suggests that functional olfactory proteins may be present in the sensory structures located on the ovipositor. Scanning electron microscopy identified five to nine porous sensilla on each of the anal papillae of the ovipositor. Furthermore, HRP immunostaining indicated that these sensilla are innervated by the dendrite-like structures from multiple neurons. Finally, we functionally characterized neural responses in these sensilla using single sensillum recordings. Stimulation with a panel of 142 monomolecular odorants revealed that these sensilla indeed house functional olfactory sensory neurons (OSNs). While it remains to be determined what role these chemosensory sensilla play in odor and gustatory guided behaviors, our data clearly demonstrate an olfactory function for neurons present in M. sexta ovipositor sensilla.